Efficacy of Saindhavadi Rasakriya Anjana in Krimigranthi with special reference to Seborrheic Blepharitis- A Case Study - Sivasankari , N; Naveen , B S; Geetha , Kumari B; Viswam, Ajoy; Namboothiri, Krishnan (International Research Journal of Ayurveda & Yoga, 2022)
Acharya Vagbhata has explained nine Sandhigata Rogas and Krimigranthi is one among them. Signs and symptoms of Krimigranthi can be analyzed with seborrheic blepharitis which is one of the commonly encountered eye lid margin diseases in OPD. Study shows that 50 percent of population develop the disease with increasing age and contact lens usage. Treatments mentioned for Krimigranthi include Swedana, Bhedana and pratisarana. This case is of a female patient who complained of itching over both eyes, foreign bodysensation, burning sensation, watering of eyes and falling of eyelashes sincetwo years which gets aggravated on exposure to dry climate, increased Visual Display Terminals (VDT) usage & reduced sleep. Anjana with Saindhavadi Rasakriya Anjana was given for 15 days. Significant reduction in signs and symptoms were observed after the treatment.